2012
DOI: 10.1109/tuffc.2012.2343
|View full text |Cite
|
Sign up to set email alerts
|

Vibro-acoustography beam formation with reconfigurable arrays

Abstract: In this work, we present a numerical study of the use of reconfigurable arrays (RCA) for vibro-acoustography (VA) beam formation. A parametric study of the aperture selection, number of channels, number of elements, focal distance, and steering parameters is presented in order to show the feasibility and evaluate the performance of VA imaging based on RCA. The transducer aperture was based on two concentric arrays driven by two continuous-wave or toneburst signals at slightly different frequencies. The mathema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…We have recently reported a simulation study of VA beamforming using a 2D reconfigurable array with elements of size 0.2 × 0.2 mm [22]. This type of transducer had elements that were small enough to greatly minimize the effects of grating lobes and would be able to focus and steer beams both in the azimuthal and elevational directions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently reported a simulation study of VA beamforming using a 2D reconfigurable array with elements of size 0.2 × 0.2 mm [22]. This type of transducer had elements that were small enough to greatly minimize the effects of grating lobes and would be able to focus and steer beams both in the azimuthal and elevational directions.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve the same aperture size in the elevation direction (10.8 mm) while using square elements that have dimension λ/2, then assuming a frequency of 8 MHz we would need 113 elements on each side of the aperture. For the full 10.8 × 10.8 mm aperture currently considered it would require 12769 elements, which is far too many for current beamformers outside of using a reconfigurable array like that studied by Kamimura et al [22]. If a lower frequency that is within the bandwidth of the transducer is considered such as 5 MHz, it would still require a total of 5041 elements (71 × 71 elements) at λ/2 spacing (0.154 mm), which is still too large a number for individually addressing each element.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A simulation study of VA using a 2D reconfigurable array has been previously reported by our research group. 37 While a 2D reconfigurable array is potentially an ideal solution for clinical implementation of VA, we have recently developed a VA system using a Q2D (in technical term, it is called 1.75D array transducer) array transducer as an intermediate step toward a desired 2D VA system. 36,38 This Q2D array US transducer has multiple rows of elements in elevation which can be electronically configured to optimally generate a close-to-symmetric ARF.…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of VA has been demonstrated for evaluating soft tissues, such as arteries (12,13), breast tissue (14,15), and prostate tissue (16). However, the implementation of VA in a commercial machine (17) and the development of new technologies for VA beam forming (18) open a new range of clinical applications.…”
Section: Introductionmentioning
confidence: 99%